Targeted Proteomics Allows Quantification of Ethylene Receptors and Reveals SlETR3 Accumulation in Never-Ripe Tomatoes - Chen, Yi; Rofidal, Valérie; Hem, Sonia; Gil, Julie; Nosarzewska, Joanna; Berger, Nathalie; Demolombe, Vincent; Bouzayen, Mondher; Azhar, Beenish J.; Shakeel, Samina N.; Schaller, G. Eric; Binder, Brad M.; et al. (Frontiers in Plant Science, 2019)
Ethylene regulates fruit ripening and several plant functions (germination, plant growth, plant-microbe interactions). Protein quantification of ethylene receptors (ETRs) is essential to study their functions, but is impaired by low resolution tools such as antibodies that are mostly nonspecific, or the lack of sensitivity of shotgun proteomic approaches. We developed a targeted proteomic method, to quantify low-abundance proteins such as ETRs, and coupled this to mRNAs analyses, in two tomato lines: Wild Type and Never-Ripe (NR) which is insensitive to ethylene because of a gain-of-function mutation in ETR3. We obtained mRNA and protein abundance profiles for each ETR over the fruit development period. We show that, despite variations between -0.2 to 1, Pearson correlations between mRNA and protein profiles are mostly positive in the WT, and that such correlations are affected by the NR mutation. Possible post-transcriptional and post-translational changes are discussed. In NR fruits, we observed the accumulation of the mutated ETR3 protein between ripening stages (Mature Green and Breaker + 8 days) which may be a cause of NR tomatoes to stay orange. The label-free analysis of membrane proteins, concomitant to Parallel Reaction Monitoring analysis, may be a resource to study changes over tomato fruit development. These results could lead to studies about ETR subfunctions and interconnections over fruit development. Variations of RNA-protein correlations may open new fields of research in ETR regulation. Finally, similar approaches may be developed to study ETRs in whole plant development and plant-microorganism interactions.